MENGKRITISI FAKTOR-FAKTOR KEGAGALAN AKADEMIK SISWA DALAM BELAJAR - Muh. Misdar (Tadrib: Jurnal Pendidikan Agama Islam, 2018)
Changes and developments in education are identical to learning. Because learning is a means to change. Changes as learning outcomes can emerge changes in physical, intellectual, emotional and behavioral changes. Not all learning can achieve the above, systematic and systematic learning that can lead to these changes. The failure of learning is one of the obstacles to change. Deep understanding of the inhibiting factors of learning is one way to overcome them. Failure to learn is a trigger for academic failure achieved by students at school. In this paper there are seven factors that lead to academic failure of students in school, among others: The active cycles experienced by students before they become the trigger for further failure, weaknesses in students in learning that are unclear what orientation and learning objectives in school, weak business those who have not yet shown a resilient effort in learning, low self-control that appears in the effort of low self-discipline in learning, lack of noble attitude that does not seem to like the heavy burden of learning, does not like challenges such as lethargy when added with assignments more learning assignments, low perceptions of learning success which usually do not have an effort to pursue higher achievement, hopes of going forward are very low. All these factors must be packaged systematically so as not to become the biggest obstacle for students in learning not to fail in school. Basically, in schools and in madrasas the teacher has implemented an effort to reduce the failure. It's just that the way teachers do is very conventional, not yet giving contributive meaning to solving student learning failures. like giving assignments or recitation. During this time the task is interpreted in a way to overcome the weaknesses of students, the task should be interpreted as a functional positive attribution to the strengthening of the results of weaknesses or failures of student learning.